Pouzití analýzy DNA v lékarství - Sedlácek, Z; Duspivová, R (Casopis lekaru ceskych, 1992)
Advances in genetic engineering influence to an increasing extent a number of medical disciplines. DNA analysis can be used in the diagnosis of hereditary diseases, in investigations of malignant processes, in forensic medicine and for detection of infectious pathogens. Two main methodical approaches to DNA analysis, Southern's method and procedures based on primer directed enzymatic amplification of DNA by the PCR method, resolve the complicated detection of slight changes in the vast volume of human genetic information. Cystic fibrosis may serve as an example of a serious hereditary disease the diagnosis of which improved greatly after introduction of DNA analysis. The diagnosis of this disease is nowadays possible by direct analysis of mutations and indirectly by investigations of the link between the disease and DNA polymorphisms.
Keywords: Polymerase Chain Reaction; cystická fibróza; Blotting, Southern; Southernův blotting; DNA; DNA Mutational Analysis; Cystic Fibrosis; polymorfismus délky restrikčních fragmentů; Genetic Diseases, Inborn; Humans; lidé; Polymorphism, Restriction Fragment Length; mutační analýza DNA; polymerázová řetězová reakce; genetické nemoci vrozené